Craniofacial Abnormalities in Hutchinson-Gilford Progeria Syndrome - Ullrich, N.J.; Silvera, V.M.; Campbell, S.E.; Gordon, L.B. (American Journal of Neuroradiology, 2012)
SUMMARY: HGPS is a rare syndrome of segmental premature aging. Our goal was to expand the scope of structural bone and soft-tissue craniofacial abnormalities in HGPS through CT or MR imaging. Using The Progeria Research Foundation Medical and Research Database, 98 imaging studies on 25 patients, birth to 14.1 years of age, were comprehensively reviewed. Eight newly identified abnormalities involving the calvaria, skull base, and soft tissues of the face and orbits were present with prevalences between 43% and 100%. These included J-shaped sellas, a mottled appearance and increased vascular markings of the calvaria, abnormally configured mandibular condyles, hypoplastic articular eminences, small zygomatic arches, prominent parotid glands, and optic nerve kinking. This expanded craniofacial characterization helps link disease features and improves our ability to evaluate how underlying genetic and cellular abnormalities culminate in a disease phenotype. CDCCenters for Disease Control and PreventionHGPSHutchinson-Gilford progeria syndromeOFCoccipitofrontal circumferenceTMJtemporomandibular jointWHOWorld Health Organization